Private vs. Public Funding for Higher Education - Altbach, Philip; de Wit, Hans; Woldegiyorgis, Ayenachew (International Higher Education, 2022)
In a growing number of countries, the private higher education sector is increasingly diverse and influential. This has not always been the case—public (state) financing and control over higher education was, with some notable exceptions, the global norm. The appropriate balance between state and nonstate participation, including funding and number of institutions, is rooted in the historical context of higher education development in each particular country, shaped by its current needs and resources.